Workplace Learning Method Preferences of Millennials in the UK - Zukhra, Wardah (2018)
Background: The Millennial Generation has started to comprise a major chunk of the UK workforce and is expected to cover majority of the global workforce by 2022. UK Millennials have expressed increasing dissatisfaction pertaining their Learning and Development plans at work. It is crucial to understand the learning method preferences of millennials to adapt to their preferences. Researchers argue that each generation has its own preferences and values, however not much academic work is available on distinct learning method preferences of millennials in the workplace. Purpose: The purpose of this research is to explore the workplace learning method preferences of millennials in the UK. Other aims were to understand the justification for workplace learning preferences of millennials and to find if other factors influence generational learning preference Method: The research adopted primary qualitative research. A total of 10 millennials, residing in the UK, with past work experience, were interviewed face-to-face, for in-depth responses. Based on the authors adaption of the 70:20:10 learning model, interviewees were asked to rank their preference between Experiential Learning methods, Social Learning methods, Formal Learning methods and Informal Learning methods and to elaborate on the reasoning for their preference choices. An insight of their perception on e-learning method was also gauged. Limitation: Generalization of results was identified as a key limitation. Conclusion: Findings indicated Millennials most preferred Experiential learning method while Social Learning method was preferred by only 2 of 10 Millennials. Amongst the unpopular learning methods, Formal Learning (some least preferred), Informal Learning (majority least preferred) and E-learning (not part of ranking), all three were only accepted by millennials when in combination with more engaging Experiential and Social learning methods. Moreover, Job design, career stage and individuals’ personality were identified as factors that influenced learning preferences apart from generational effect. The practical and future implications of this study are presented in the conclusion section of this research.